Assessment of the risk for tuberculosis in the treatment of psoriasis with biologics: a multicenter retrospective study of 2 704 cases - Xia YOU; Jianjian ZHU; Ping HE; Jian LONG; Xiaojiao ZHAO; Xiaoxiao CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To provide the evidence base for the safety of biologics in the treatment of psoriasis, we retrospectively analyzed tuberculosis (TB) infection and its activation in psoriatic patients treated with biologics. Methods Information of 2 704 psoriatic patients treated with biologics was collected from the database of the National Standardized Diagnosis and Treatment Center for Psoriasis from June 2020 to January 2022. Data analyses included patients' general conditions, results of TB screening (PPD, QFT, chest X-ray and/or chest CT), preventive anti-TB treatment, and monitoring and activation of TB infection during the treatments. Results Out of 2 704 subjects, 436 (16.12%) cases were treated with TNF-α inhibitors, while 82.84% (2 240) and 1.04% (28) of the patients were treated with IL-17A inhibitors and IL-12/23 inhibitor, respectively. Prior to biological treatment, 898 (33.21%) cases were screened for TB, among which 85 (9.46%) cases were TB positive. Out of the 85 cases with TB positive, 20 cases were treated with isoniazid + rifampicin for 3 months, and 3 cases received mono-isoniazid treatment for 6 months. During the follow-up, TB reactivation was observed in 2 cases (2/200, 1%), which both received TNF-α inhibitor (adalimumab). Conclusions Prior to biological treatments, only small portion of psoriatic patients receive TB screening and anti-TB treatment in China. Although the risk for TB reactivation is relatively low during biological treatment, TNF-α inhibitors have a higher risk for TB reactivation compared to other biologics. Thus, screening for LTBI before biological therapy and monitoring TB reactivation during biological therapy are still crucial in the treatment of psoriasis with biologics, particularly TNF-α inhibitors.